First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

What Is a Specialist? Quantifying Host Breadth Enables Impact Prediction for Invasive Herbivores - Ashley N. Schulz; Nathan P. Havill; Travis D. Marsico; Matthew P. Ayres; Kamal J.K. Gandhi; Daniel A. Herms; Angela M. Hoover; Ruth A. Hufbauer; Andrew M. Liebhold; Kenneth F. Raffa; Kathryn A. Thomas; Patrick C. Tobin; et al. (Ecology Letters, 2025)
Herbivores are commonly classified as host specialists or generalists for various purposes, yet the definitions of these terms, and their intermediates, are often imprecise and ambiguous. We quantified host breadth for 240 non‐native, tree‐feeding insects in North America using phylogenetic diversity. We demonstrated that a partitioning of host breadth: (1) causes 67% of non‐native insects to shift from a generalist to specialist category, (2) displays a reduction in host breadth from the native to introduced range, (3) identifies an inflection point in a model predicting the likelihood of non‐native insect ecological impact, with a corresponding change in behaviour associated with specialists versus generalists, and (4) enables three models for strong prediction of whether a non‐native forest insect will cause high impacts. Together, these results highlight the primacy of how herbivore host recognition and plant defences mediate whether novel host interactions will result in high impact after invasion.

Smallholder farmers’ diverse values in maize landrace conservation: A case study from Chiapas, Mexico - Ana Sofía Monroy-Sais; Daniel Tobin; Mauricio R. Bellon; Marta Astier; Angélica Cibrián-Jaramillo; Nancy Gálvez-Reyes; Alicia Mastretta-Yanes; Jorge Ruiz-Arocho; Ana Wegier; Yolanda H. Chen (Journal of Rural Studies, 2024)

The association between crop diversity and children’s dietary diversity: multi-scalar and cross-national comparisons - Carina Isbell; Daniel Tobin; Brian C. Thiede; Kristal Jones; Travis Reynolds (Food Security, 2024)
Food insecurity is rising across sub-Saharan Africa (SSA), where undernourishment continues to affect a large portion of the population, particularly young children. Studies examining the associations between crop diversity and childhood nutrition have recently proliferated but are characterized by inconsistent results and two key limitations. First, many studies focus only on the household level, overlooking the prospect that more diverse crops at village and regional levels may contribute to household food security. Second, many studies pool data from multiple countries, which may obscure important context-specific aspects of nutrition outcomes. Drawing on Demographic and Health Survey (DHS) data from 10 SSA countries, in combination with agricultural production estimates for 112 crop species, this study explores the associations between crop diversity at multiple scales (10-, 25-, and 50-kilometer radii) and children’s dietary diversity (HDDS). In addition to producing overall estimates across our sample, we measure country-specific associations to account for spatial heterogeneity. Results of the overall model show a negative association between crop diversity and dietary diversity. However, the country-specific analyses uncover extensive variability in these associations: in some cases, diversity is highly positively correlated with HDDS, while in others the estimated effect is negative or nonexistent. Our findings suggest that country-level analyses provide important nuance that may be masked in pooled analyses. Moreover, these findings foreground the importance of looking beyond household-level analyses to understand the dynamic role that local crop diversity, and its exchange across space, can play in supporting children’s dietary diversity.

Diagenesis of fossil gar fish scales with implications for geochronology and paleoenvironmental applications - John Fink; Marissa M. Tremblay; Thomas S. Tobin; Lisa D. Stockli; Daniel F. Stockli; Ryan B. Ickert (Geochimica et Cosmochimica Acta, 2024)

Market engagement, crop diversity, dietary diversity, and food security: evidence from small-scale agricultural households in Uganda - Katherine Morrissey; Travis Reynolds; Daniel Tobin; Carina Isbell (Food Security, 2024)
Small-scale farmers make up the majority of farmers worldwide yet experience particularly high rates of food insecurity. A growing body of literature explores pathways to food and nutrition security among small-scale farmers but has yet to reach consensus on the most effective pathways (e.g., crop specialization for market sale versus on-farm crop diversification for home consumption) to improve livelihoods. Using structural equation modelling (SEM) based on data drawn from the 2015/16 Uganda National Panel Survey, this study considers how farm and household characteristics including gender, age, education, farm size, region, and off-farm income relate to market engagement (farm sales, market purchases) and on-farm crop diversity (Simpson’s diversity). We then further examine how market engagement and on-farm crop diversity relate to household livelihood outcomes including dietary diversity and food security (number of food secure months). Findings suggest that both higher levels of market engagement and on-farm crop diversity are associated with increased dietary diversity. Higher levels of crop diversity—whether for market sale or for self-consumption—are strongly associated with improved food security. Market engagement is positively associated with increased dietary diversity, and this association is particularly strong for market purchases. Together, these findings highlight the potential for both market-based strategies and on-farm crop diversity to contribute to food security goals in Uganda, providing further evidence that these strategies can be complementary.

Optimization of Cobalt Chrome 3D re-entrant Auxetics fabricated using Selective Laser Melting - Daljeet Singh; Daniel Tobin; Luke Dowling; Daniel Trimble (Engineering Structures, 2023)

Ruminative reflection is associated with anticorrelations between the orbitofrontal cortex and the default mode network in depression: implications for repetitive transcranial magnetic stimulation - Tobin J. Ehrlich; Jyoti Bhat; Andrea M. Horwege; Daniel H. Mathalon; Gary H. Glover; Brian J. Roach; Bashar W. Badran; Steven D. Forman; Mark S. George; J. Cobb Scott; Michael E. Thase; Jerome A. Yesavage; et al. (Brain Imaging and Behavior, 2022)
Patients with depression who ruminate repeatedly focus on depressive thoughts; however, there are two cognitive subtypes of rumination, reflection and brooding, each associated with different prognoses. Reflection involves problem-solving and is associated with positive outcomes, whereas brooding involves passive, negative, comparison with other people and is associated with poor outcomes. Rumination has also been related to atypical functional hyperconnectivity between the default mode network and subgenual prefrontal cortex. Repetitive pulse transcranial magnetic stimulation of the prefrontal cortex has been shown to alter functional connectivity, suggesting that the abnormal connectivity associated with rumination could potentially be altered. This study examined potential repetitive pulse transcranial magnetic stimulation prefrontal cortical targets that could modulate one or both of these rumination subtypes. Forty-three patients who took part in a trial of repetitive pulse transcranial magnetic stimulation completed the Rumination Response Scale questionnaire and resting-state functional magnetic resonance imaging. Seed to voxel functional connectivity analyses identified an anticorrelation between the left lateral orbitofrontal cortex (−44, 26, −8; k = 172) with the default mode network-subgenual region in relation to higher levels of reflection. Parallel analyses were not significant for brooding or the RRS total score. These findings extend previous studies of rumination and identify a potential mechanistic model for symptom-based neuromodulation of rumination.

Predicting non-native insect impact: focusing on the trees to see the forest - Ashley N. Schulz; Angela M. Mech; Matthew P. Ayres; Kamal J. K. Gandhi; Nathan P. Havill; Daniel A. Herms; Angela M. Hoover; Ruth A. Hufbauer; Andrew M. Liebhold; Travis D. Marsico; Kenneth F. Raffa; Patrick C. Tobin; et al. (Biological Invasions, 2021)

Determinants of successful arthropod eradication programs - Patrick C. Tobin; John M. Kean; David Maxwell Suckling; Deborah G. McCullough; Daniel A. Herms; Lloyd D. Stringer (Biological Invasions, 2014)

When one is not necessarily a lonely number: initial colonization dynamics of Adelges tsugae on eastern hemlock, Tsuga canadensis - Patrick C. Tobin; Richard M. Turcotte; Daniel A. Snider (Biological Invasions, 2013)

Methylacridinium and its Cholinergic Properties - Ondrej Soukup; Jan Proska; Jiri Binder; Jana Zdarova Karasova; Gunnar Tobin; Daniel Jun; Jan Marek; Kamil Musílek; Josef Fusek; Kamil Kuca (Neurotoxicity Research, 2009)

A Literal Use of “Forest Health” Safeguards against Misuse and Misapplication - Kenneth F. Raffa; Brian Aukema; Barbara J. Bentz; Allan Carroll; Nadir Erbilgin; Daniel A. Herms; Jeffrey A. Hicke; Richard W. Hofstetter; Steven Katovich; B. Staffan Lindgren; Jesse Logan; William Mattson; et al. (Journal of Forestry, 2009)